Formation of the communicative culture of preschoolers using game activity - Shcherbakova, Anna Iosifovna (2021)
The study examines the most significant problems associated with the formation of the communicative culture of preschool children. The main attention is paid to gaming technologies that have a high level of pedagogical efficiency. The reasons for the emergence of problems in the communicative interactions of preschoolers are analyzed; the theoretical foundations in the organization of research aimed at creating a play space that forms the communicative culture of preschool children are proposed. Organizational and pedagogical conditions for the development of the communication skills of preschoolers are highlighted, among which are game technologies that use the capabilities of theatrical art, which can become the basis for the functional development of a preschooler’s personality and their ability to fully communicate with others. On the other hand, the very communicative culture of preschool children is assessed as a mechanism of their socialization and inculturation. The study provides a typology of gaming technologies that are relevant for the development of individual communication skills and the general personal development of children of this age. The study may be of interest to a wide range of specialists in the field of preschool pedagogy, psychology, and children’s art.